2011
DOI: 10.2174/138620711796504442
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Luminescence ADP Production Assay and Radiometric Scintillation Proximity Assay for Cdc7 Kinase

Abstract: Several assay technologies have been successfully adapted and used in HTS to screen for protein kinase inhibitors; however, emerging comparative analysis studies report very low hit overlap between the different technologies, which challenges the working assumption that hit identification is not dependent on the assay method of choice. To help address this issue, we performed two screens on the cancer target, Cdc7-Dbf4 heterodimeric protein kinase, using a direct assay detection method measuring [33P]-phosphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 32 publications
(49 reference statements)
0
17
0
Order By: Relevance
“…19 The Z 0 factor constitutes a dimensionless parameter that ranges from 1 (infinite separation) to < 0. It is defined as Z 0 = 1 -(3sc + + 3sc -) / jmc + -mc -j, where sc + , sc -, mc + , and mc -are the standard deviations (s) and averages (m) of the high (c + ) and low (c -) control.…”
Section: Dose-response Study Of Primary Positives With the Spa Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…19 The Z 0 factor constitutes a dimensionless parameter that ranges from 1 (infinite separation) to < 0. It is defined as Z 0 = 1 -(3sc + + 3sc -) / jmc + -mc -j, where sc + , sc -, mc + , and mc -are the standard deviations (s) and averages (m) of the high (c + ) and low (c -) control.…”
Section: Dose-response Study Of Primary Positives With the Spa Methodsmentioning
confidence: 99%
“…The Z 0 factor between 0 and 0.5 indicates a marginal assay and < 0 signifies a poor assay with overlap between controls. 19 …”
Section: Dose-response Study Of Primary Positives With the Spa Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Instead, the study showed that a glutamic acid (Glu217) has replaced the threonine, making Cdc7 an atypical member of the serine/threonine kinase family. 23 Using a luciferase-based assay that has previously been successfully utilized to assay Cdc7 activity, 24 we compared the relative kinase activities of Cdc7 WT , Cdc7 £5A , Cdc7 £5D and Cdc7 T376A in relation to the Cdc7 1-431 negative control, an allele that is deleted for its Dbf4 interacting domain. 34 Under our experimental conditions, all three mutant alleles (Cdc7 £5A , Cdc7 £5D and Cdc7 T376A ) showed substantial kinase activity close to the level of wild type, although the difference in kinase activities between the mutants and Cdc7 WT are still significant (Fig.…”
Section: Cdc7 Is Phosphorylated During Prometaphase In a Cdk1-dependementioning
confidence: 99%
“…21,22 Finally, other groups have successfully used recombinant human DDK in in vitro kinase assays in the absence of Cdk phosphorylation. 23,24 Thus, the significance and function of Cdk-dependent Cdc7 phosphorylation in vivo is still to be unambiguously determined.…”
Section: Introductionmentioning
confidence: 99%